2020
DOI: 10.1002/jmv.26659
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 in Argentina: Lockdown, mobility, and contagion

Abstract: There is a debate in Argentina about the effectiveness of mandatory lockdown policies containing severe acute respiratory syndrome coronavirus type 2 disease. This policy has already 6 months long making it one of the longest in the world. The population effort to comply with the lockdown has been decreasing over time given the economic and social costs that it entails. This contribution analyzes the relationship between mobility and contagion in Argentina at a provincial level. It also models issues of intern… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 22 publications
3
28
0
Order By: Relevance
“…Non-pharmaceutical interventions have been shown to reduce the number of COVID-19 cases [13], the contagion rate [18], the reproductive number [13,15,16], the case fatality rate [17] and the number of SARS-CoV-2 introductions and/or exportations [19,20,35]. Here we showed that international movement is negatively correlated with frequency change of HF mutations (Fig.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Non-pharmaceutical interventions have been shown to reduce the number of COVID-19 cases [13], the contagion rate [18], the reproductive number [13,15,16], the case fatality rate [17] and the number of SARS-CoV-2 introductions and/or exportations [19,20,35]. Here we showed that international movement is negatively correlated with frequency change of HF mutations (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Different studies have evaluated the relationship between non-pharmaceutical interventions and the decrease in the number of cases [13,14], the reproductive number [13,15,16], the case fatality rate [17], the contagion rate [18], and the number of SARS-CoV-2 importations [19,20]. On the other hand, the effect of non-pharmaceutical interventions, particularly those related to an international movement, on mutation frequency variation has been less analyzed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some countries opted for more liberal approaches to tackle COVID-19, such as Sweden, which relied mostly on responsible behavior, others maintained very strict curfews for extended periods (eg. Argentina) ( 35 ). A reasonable goal should be to keep the health care system below its capacity level, albeit our algorithm permits tuning the parameter Q to make stringency ( u ( t )) more or less flexible, which ultimately impacts economic sectors and social behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, mobility was inferred as the main cause of the outbreak dynamics, at least in the first wave in Japan [9] and throughout the world [10][11][12][13]. This study was conducted to estimate vaccine coverage effects on SARS-CoV-2 infectiousness for the outbreak in Japan.…”
Section: Introductionmentioning
confidence: 99%